Ampullary and Periampullary Adenocarcinoma: New Challenges in Management of Recurrence - Ramfidis, Vassilis Stefanos; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
The mainstay treatment of ampullary and periampullary adenocarcinoma is pancreaticoduodenectomy. Unfortunately, there are no standard options available in the postoperative management due to the rarity of the malignancy and the absence of prospective trials. In this year ASCO Gastrointestinal Cancers Symposium three remarkable abstracts regarding the management of recurrent or metastatic ampullary and periampullary carcinoma were presented. The first study (Abstract #257) demonstrates that palliative reoperation should not be an option, because of its severe morbidity and high mortality. The second study (Abstract #317) supports that reirradiation is well tolerated and it could be used for palliative reasons and local control. The last study (Abstract #197) reveals the prognostic value of 92-gene RT-PCR assay and the authors support the use of this method for the management of metastatic periampullary adenocarcinoma when the primary pathological sample cannot be helpful. Image: 251 Airforce General Hospital. Athens, Greece